The evolution and determination of earnings inequality in post-apartheid South Africa - Arden Finn; Murray Leibbrandt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this paper we identify some of the drivers of changes in the distribution of earnings and earnings inequality in the South African labour market between 2000 and 2014. Although the overall level of earnings inequality between 2000 and 2011 was high and relatively stable, there were nonetheless some interesting shifts in the factors generating inequality. The earnings data from mid-2012 to 2014, however, show a steep increase in inequality. It is difficult to determine how much of this is a "real" change, and how much is driven by other factors such as measurement error and changes in data collection and processing. For this reason, all results are presented in a 2000-14, 2000-11, and 2011-14 format. We use RIF regressions to decompose changes in average earnings, as well as changes in the Gini coefficient and different percentile ratios. Our main finding is that changes in the returns to education and changes in the returns to potential experience were the most important determinants of changes in inequality, with the former generally being inequality-enhancing, and the latter inequality-reducing.
Keywords: D31; J31; 330; RIF decomposition; South Africa; wage inequality